Training agility over 60-180° turns: Underpinning mechanics and the synergy of base of support, center of mass, and direction of force - Turner, A. N. (Strength and Conditioning Journal, 2026)
For many athletes, being agile is the end goal of physical performance training. It represents their capacity to change velocity and direction in response to the actions of their opponent and the opportunities and constraints of their environment. The aim of this article was to describe the pitch-based development of agility, focusing on 60-180° turns. This ensures all turns have the demand of deceleration, turning, and reacceleration, requiring both outside leg turns (60°) and inside leg turns (180°). To enable the effective coaching of these, coaches must understand movement mechanics and thus the fundamental principles that underpin good technique. Within agility training, a detailed appreciation of how the center of mass and base of support interact to affect the direction of force is fundamental to this. This understanding and the ensuing technical models ensure athletes have the best chance of executing the task optimally and ensure coaches can effectively instruct athletes and adapt drills accordingly.